2022
DOI: 10.3390/life12081209
|View full text |Cite
|
Sign up to set email alerts
|

Tunicamycin-Induced Endoplasmic Reticulum Stress Damages Complex I in Cardiac Mitochondria

Abstract: Background: Induction of acute ER (endoplasmic reticulum) stress using thapsigargin contributes to complex I damage in mouse hearts. Thapsigargin impairs complex I by increasing mitochondrial calcium through inhibition of Ca2+-ATPase in the ER. Tunicamycin (TUNI) is used to induce ER stress by inhibiting protein folding. We asked if TUNI-induced ER stress led to complex I damage. Methods: TUNI (0.4 mg/kg) was used to induce ER stress in C57BL/6 mice. Cardiac mitochondria were isolated after 24 or 72 h followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 67 publications
3
15
0
Order By: Relevance
“…The induction of acute ER stress damages the ETC in C57BL/6 mice. 1,9,19 In the present study, we find that TUNI-induced ER stress damages the ETC in tamoxifentreated CPNS1 PZ/PZ control mice but not in CPNS1 cardiacspecific deletion mice. TUNI treatment activates both cCPN1/2 and mCPN1/2 in control mice.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…The induction of acute ER stress damages the ETC in C57BL/6 mice. 1,9,19 In the present study, we find that TUNI-induced ER stress damages the ETC in tamoxifentreated CPNS1 PZ/PZ control mice but not in CPNS1 cardiacspecific deletion mice. TUNI treatment activates both cCPN1/2 and mCPN1/2 in control mice.…”
Section: Discussionsupporting
confidence: 46%
“…Our previous study showed that 72 h after a one-time TUNI treatment that ER stress was increased accompanied by mitochondrial dysfunction and damage to the ETC in C57BL/6 mice. 9 Therefore, TUNI was used in the current study to induce ER stress in control and CPNS1 T A B L E 5 ER stress induced by tunicamycin (TUNI) treatment led to an increase in select mitochondrial protein contents in control but not in deletion mice. deletion mice to test the hypothesis that CPN1/2 was a critical effector of ER stress-mediated mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 A recent in vivo study found that TN treatment activates both cytosolic and mitochondrial calpain 1 (CAPN-1). 16 In a study investigating the antitumor effect of TN, it was also found that TN inhibits cell proliferation and migration in hepatocellular carcinoma. 17 In our study, we examined the effect of TN…”
Section: Discussionmentioning
confidence: 99%